PENGARUH PENERAPAN MODEL PEMBELAJARAN GUIDED DISCOVERY TERHADAP PENCAPAIAN KOMPETENSI IPA TERPADU PESERTA DIDIK KELAS VIII SMPN 30 PADANG - Monika Putri; Mahrizal Mahrizal; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2016)
Factors that cause the low learning outcomes of integrated science are learning model used. Factors that useful to improve the competence of attitude, knowledge and skills. The purposes of this study was to determine differences in the achievement of the integrated IPA competence of learners between guided  discovery learning model with a nuanced conventional scientific approach. This type of research is Quasi Experiment Research and design research that only randomized control group design. Population of this research was all students from grade VIII in junior high school 30 Padang registered on 2015/2016. Population based sampling technique is purposive sampling and cluster sampling. Data collection technique to aspects of knowledge that is a written test or tes objective, for the attitude aspects is the observation sheet and to aspects of that assessment skills to work. This study shows that control class. Thus the results of this study stated there are differences in the achievement of the integrated science competence among learners using guided discovery learning and nuances of the conventional scientific approach to grade VIII in junior high school 30 Padang